Contagious charisma: the flow of charisma from leader to followers and the role of followers’ self-monitoring - Katz-Navon, Tal; Delegach, Marianna; Haim, Eden (Frontiers in Psychology, 2023)
Charisma, the captivating attribute that endows an individual with the power to inspire and influence others, is frequently associated with possessing an attractive personality, effective communication skills, and the capacity to draw people in and lead them. The concept of the trickle-down effect in leadership theory suggests that the characteristics of a leader’s style including perceptions, emotions, attitudes, and behaviors, have the potential to be “contagious” and spread to their followers. Nevertheless, it is unclear whether and when a leader’s charisma may be transferred to followers, as charisma is predominantly a trait associated with the leader. Integrating insights from the social learning, emotional contagion, and self-concept theories, we propose that charisma can cascade downward from the leader to followers and that this effect is contingent on the individual follower’s level of self-monitoring. Measuring a sample of 127 followers and 15 leaders in a large organization at two time points, we found that throughout time the leader’s charisma indeed cascaded down to followers, i.e., followers of a charismatic leader were perceived as more charismatic throughout time. However, this effect was prominent only for low-monitoring followers. Novel insights into the flow-down effect of charisma, avenues for future research, and practical implications are discussed.